Sequential and simultaneous thermal and particle exposure of tungsten. (21st January 2016) - Steudel, I; Huber, A; Kreter, A; Linke, J; Sergienko, G; Unterberg, B; Wirtz, M
Abstract: The broad array of expected loading conditions in a fusion reactor such as ITER necessitates high requirements on the plasma facing materials (PFMs). Tungsten, the PFM for the divertor region, the most affected part of the in-vessel components, must thus sustain severe, distinct exposure conditions. Accordingly, comprehensive experiments investigating sequential and simultaneous thermal and particle loads were performed on double forged pure tungsten, not only to investigate whether the thermal and particle loads cause damage but also if the sequence of exposure maintains an influence. The exposed specimens showed various kinds of damage such as roughening, blistering, and cracking at a base temperature where tungsten could be ductile enough to compensate the induced stresses exclusively by plastic deformation (Pintsuk et al 2011 J. Nucl. Mater. 417 481–6 ). It was found out that hydrogen has an adverse effect on the material performance and the loading sequence on the surface modification.